National Exams and Education Problems in Indonesia: Critical Study an Instrument for Improving the Quality of Education - Syahidu, Andrian; Suryadi, Adi; Hadi, Samsul (Proceeding International Conference on Religion, Science and Education, 2022)
The National Examination (UN) as an instrument for evaluating middle-level education in Indonesia always gets the spotlight from various parties. This is inseparable from the imbalance of education that occurs in the center and outermost and isolated areas in this country. So that makes the UN difficult to evaluate thoroughly the abilities of existing students. Therefore this paper tries to examine the extent to which the National Examination acts as an instrument capable of improving the quality of national education. Moreover, the development of evaluation systems offered by other countries, this can be seen as applied in developed countries. Furthermore, the existence of the COVID-19 pandemic that has hit the all over the world. Then, will the system that has been built by the government be maintained or will it use different evaluation instruments to improve the quality of education. This problem will be reviewed from the extent of the positive and negative impacts caused by this evaluation instrument with an analysis of the direct impact of the National Examination on the condition of education and students as the object of the education being carried out.